Bisinglah! BEB (Belia Elak Bising): The development of Malay version of Educational Hearing Conservation Programme (EdHCP) for youth - Akmal, Kamarul; Ismail, Noraidah; Rahmat, Sarah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Exposure to leisure noise in youth has become a public health concern. Excessive noise exposure might lead to permanently damaged outer hair cells (OHCs) which caused noise-induced hearing loss (NIHL). It has been reported that attitudes and behaviours are important factors in determining how well someone is taking care of their ears. Therefore, it is essential to implement a hearing healthcare programme to address this problem. The main objective of the current study is to develop and validate a Malay version of educational hearing conservation programme (EdHCP) for students at high school, college or/and university. A cross-sectional study is conducted among students in Kolej Tingkatan 6, Desa Murni Butterworth. This programme involved 3 phases: 1) reviewing and adapting of EdHCP, 2) content-validity from 10 expert panels, and 3) a 50- minutes classroom session for 40 students. The contents of this module are basic information of the ear, dangerous noise and hearing preventive measures. Bisinglah! BEB (Belia Elak Bising)™ has been modified based on the reviews and comments from the content validation index (CVI) and content validation ratio (CVR). The S-CVI/Ave value is high, at 0.935 and agreement among the students in pre-testing were excellent. The contents and layout of the newly developed Malay EdHCP known as â€˜Bisinglah! BEB (Belia Elak Bising)™ are relevant, informative and produced a high value of content-validity finding. However, further study is needed to investigate the effectiveness of the programme among Malaysian youth.